2010
DOI: 10.1016/j.ctrv.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the pregnant mother with cancer: A systematic review on the use of cytotoxic, endocrine, targeted agents and immunotherapy during pregnancy. Part I: Solid tumors

Abstract: The association of cancer and pregnancy is increasingly encountered nowadays in clinical practice. Due to the relative rarity of the situation, it lacks a systematized approach. Different systemic therapies are used in managing cancer with uncertainty regarding the potential hazards they could pose on the pregnancy and/or the fetus. We have performed a systematic review of literature to identify all reports addressing cancer patients who were exposed to any of the known systemic therapies during the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 117 publications
0
73
0
1
Order By: Relevance
“…Termination of ongoing pregnancy or delay of required treatment should be discussed with the patient according to time of pregnancy and patient's preference [2,6,15] . The first trimester of pregnancy is not appropriate for chemotherapy because of high risk of fetal malformations [16] . While it is generally recommended that chemotherapy should be given only after delivery, there are some reports suggesting that chemotherapy can be given in the second trimester without causing significant longterm complications [6,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Termination of ongoing pregnancy or delay of required treatment should be discussed with the patient according to time of pregnancy and patient's preference [2,6,15] . The first trimester of pregnancy is not appropriate for chemotherapy because of high risk of fetal malformations [16] . While it is generally recommended that chemotherapy should be given only after delivery, there are some reports suggesting that chemotherapy can be given in the second trimester without causing significant longterm complications [6,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…154 Cervical, breast, thyroid, and ovarian cancers, melanoma, lymphoma, and leukemia are the most common cancers diagnosed during pregnancy. [155][156][157][158] These are also the most common cancers diagnosed in the AYA population. 159 An analysis of 1963 to 2007 data from the Swedish Multi-Generation Register and the National Cancer Register showed a lower-than-expected number of cancers diagnosed during pregnancy, and a rebound in the number of cases of melanoma, CNS cancers, breast cancer, and thyroid cancer in postpartum women.…”
Section: Management Of Cancer During Pregnancymentioning
confidence: 99%
“…15 Recognized as teratogenic and mutagenic, antineoplastic agents act on rapidly proliferating cells and are therefore of particular concern for a developing fetus. [16][17][18] Previous studies have had mixed results, and many suffer from limited sample sizes. The three largest studies [19][20][21] showed increased risks for spontaneous abortion with self-reported first trimester exposure through handling or mixing, mostly among oncology nurses or pharmacists (ORs ranging from 1.5-2.3) in samples that included from 18 to 223 exposed cases.…”
Section: Commentmentioning
confidence: 99%